Over and over. (Economist, 2026)
The article examines the prospect of artificial intelligence achieving recursive self-improvement, where models build faster and more capable successors without human involvement, potentially leading to superintelligence. Topics include recursive self-improvement timelines, automation of artificial intelligence research and development; and physical constraints like computing power and training data.